The music of Ayser Vanҫin - Crawford, Taylor Dawn (Kansas State University, 2021)
The purpose of this report is to explore and examine select works by the Turkish composer Ayser Vanҫin. This document includes a composer biography; an in depth analysis of four works: The Nine Muses (for solo oboe and English horn), Orient Express - Route 2 (for oboe and piano), Canto Beduino (for Baritone, oboe, and guitar), and Albatrò (for Baritone, oboe, and piano); an overview of her compositional style and salient features found throughout her works; an interview with Vanҫin; and a complete listing of her compositions. Special attention is given to literature included with or alluded to in each work, as bringing life to words through music is one of Vanҫin’s main goals of composition.
Keywords: Music; Oboe; Ayser Vanҫin; Women in music; English horn